An Improved Polymerase Cross-Linking Spiral Reaction Assay for Rapid Diagnostic of Canine Parvovirus 2 Infection - Xu, Xin; Wang, Xueyu; Hu, Wen; Wu, Qianqian; Yao, Lunguang; Kan, Yunchao; Ji, Jun; Bi, Yingzuo (Frontiers in Veterinary Science, 2020)
With increasing complications of canine parvovirus infection cases, disease diagnosis and treatment have become more difficult. In this study, specificity primers for the conserved region of the VP2 gene of CPV-2 were synthesized and evaluated. An improved polymerase cross-linking spiral reaction (PCLSR) method for early and rapid diagnosis of CPV-2 was established. The results showed that the amplification reaction was optimal when run at 62 °C for 50 min and could be used to detect CPV-2 without any cross-reactions with other pathogens of canine infectious diseases. Reaction results were directly judged by naked eyes, with the positive amplification tube shown as luminous yellow and the negative tube as bright purple. Compared with the previously reported PSR method for CPV-2 detection, this reaction was performed using improved primer pairs and a better dye identification method (using an indicator comprising phenol red and cresol red). The detection limit of PCLSR was 3.9 × 101 copies using gel electrophoresis or a visible dye. The positive rate of 132 clinical samples was 42.42%, which was identical the same as that of the PSR method and slightly higher than that of the colloidal gold strip (39.39%). The newly developed CPV-PCLSR assay shows the advantage of rapid visualization of results and offers a convenient and rapid method for early CPV-2 diagnosis with higher sensitivity and specificity than the established methods.